Potency of Human Cardiosphere-Derived Cells from Patients with Ischemic Heart Disease Is Associated with Robust Vascular Supportive Ability. (16th February 2017) - Harvey, Emma; Zhang, Huajun; Sepúlveda, Pilar; Garcia, Sara P.; Sweeney, Dominic; Choudry, Fizzah A.; Castellano, Delia; Thomas, George N.; Kattach, Hassan; Petersen, Romina; Blake, Derek J.; Taggart, David P.; et al.
Abstract: Cardiosphere-derived cell (CDC) infusion into damaged myocardium has shown some reparative effect; this could be improved by better selection of patients and cell subtype. CDCs isolated from patients with ischemic heart disease are able to support vessel formation in vitro but this ability varies between patients. The primary aim of our study was to investigate whether the vascular supportive function of CDCs impacts on their therapeutic potential, with the goal of improving patient stratification. A subgroup of patients produced CDCs which did not efficiently support vessel formation (poor supporter CDCs), had reduced levels of proliferation and increased senescence, despite them being isolated in the same manner and having a similar immunophenotype to CDCs able to support vessel formation. In a rodent model of myocardial infarction, poor supporter CDCs had a limited reparative effect when compared to CDCs which had efficiently supported vessel formation in vitro. This work suggests that not all patients provide cells which are suitable for cell therapy. Assessing the vascular supportive function of cells could be used to stratify which patients will truly benefit from cell therapy and those who would be better suited to an allogeneic transplant or regenerative preconditioning of their cells in a precision medicine fashion. This could reduce costs, culture times and improve clinical outcomes and patient prognosis.